Persistent human bocavirus 1 infection and tonsillar immune responses - Ivaska Lotta E.; Silvoniemi Antti; Palomares Oscar; Turunen Riitta; Waris Matti; Mikola Emilia; Puhakka Tuomo; Söderlund-Venermo Maria; Akdis Mübeccel; Akdis Cezmi A.; Jartti Tuomas (WILEY, 2025)
Background Persistent human bocavirus 1 (HBoV1) infection is a common finding in patients suffering from chronic tonsillar disease. However, the associations between HBoV1 infection and specific immune reactions are not completely known. We aimed to compare in vivo expression of T-cell cytokines, transcription factors, and type I/III interferons in human tonsils between HBoV1-positive and -negative tonsillectomy patients.
Methods Tonsil tissue samples, nasopharyngeal aspirate (NPA), and serum samples were obtained from 143 immunocompetent adult and child tonsillectomy patients. HBoV1 and 14 other respiratory viruses were detected in NPAs and tonsil tissues by polymerase chain reaction (PCR). Serology and semi-quantitative PCR were used for diagnosing HBoV1 infections. Expression of 14 cytokines and transcription factors (IFN-alpha, IFN-beta, IFN-gamma, IL-10, IL-13, IL-17, IL-28, IL-29, IL-37, TGF-beta, FOXP3, GATA3, RORC2, Tbet) was analyzed by quantitative reverse-transcription (RT)-PCR in tonsil tissues.
Results HBoV1 was detected by PCR in NPA and tonsils from 25 (17%) study patients. Serology results indicated prior nonacute infections in 81% of cases. Tonsillar cytokine responses were affected by HBoV1 infection. The suppression of two transcription factors, RORC2 and FOXP3, was associated with HBoV1 infection (p < 0.05). Furthermore, intratonsillar HBoV1-DNA loads correlated negatively with IFN-lambda family cytokines and IL-13.
Conclusions Our study shows distinctively decreased T-helper(17) and T-regulatory type immune responses in local lymphoid tissue in HBoV1-positive tonsillectomy patients. HBoV1 may act as a suppressive immune modulator.